18F‐FAPI versus 18F‐FDG PET/CT in the Diagnosis of Relapsing Polychondritis - Xiaotong Guo; Juan Chen; Qian Zhao; Ying Liu; Xiuyan Wang (Clinical Case Reports)
ABSTRACT Relapsing polychondritis (RP) is a rare immune‐mediated systemic inflammatory disease with diverse clinical manifestations. Independent involvement of the respiratory system in RP is uncommon. In the event of respiratory involvement as the initial airway‐only manifestation, the diagnosis of RP is challenging and might be delayed, and patients with respiratory involvement exhibit a poor prognosis. However, no specific diagnostic method is currently available for RP with respiratory system involvement as the main clinical manifestation. We present a 49‐year‐old female with the complaint of chronic dry cough accompanied by shortness of breath after exercise that has persisted for over a year. The patient was treated using corticosteroids. The patient's symptoms improved rapidly with the administration of 5 days of methylprednisolone sodium succinate at a dose of 40 mg/day. The treatment was then switched to methylprednisolone tablets at a dose of 40 mg/day, and the dosage was reduced by 4 mg every week until the cessation of therapy. Meanwhile, oral cyclophosphamide tablets were administered once every day at a dose of 100 mg each time. After 1 month of treatment, the symptoms of cough disappeared, the modified british medical research council (mMRC) grade dropped from 4 to 2, and the COPD assessment test (CAT) score dropped from 30 to 17. Repeated CT of the chest revealed that the tracheal wall thickening had alleviated. No recurrence was revealed in the follow‐up visit 12 months after drug withdrawal. The patient underwent 18F‐FDG PET/CT examination before hormone and immunosuppressive therapy, and 18F‐FAPI PET/CT examination was performed 5 days later. The 18F‐FDG PET/CT method revealed slight thickening of the local wall of the trachea and the left and right main bronchus, with no increase in the FDG metabolism, and no abnormalities in the rest of the cartilage. 18F‐FAPI PET‐CT imaging showed increased FAPI uptake in various parts of the body, including trachea and bronchus. The present study reports that compared to 18F‐FDG PET/CT, the 18F‐FAPI PET/CT revealed more lesions and provided a better image contrast, suggesting the latter as a suitable diagnostic method for RP, which could assist in improving the clinical management of RP patients.